Crop-Livestock Integration in a Competitive, Sustainable and Democratize Agribusiness Development - Kusuma Diwyanto; Bambang R Prawiradiputra; Darwinsyah Lubis (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2002)
The concept of integrated crop and livestock in Indonesian farming systems has actually been practiced by farmers since they familiar with farming, but they practiced  the systems by traditional way, without any consideration of cost-benefit as well as environmental impact. The research on crops-livestock systems has been conducted systematically since early 1980’s. The study considered many aspects in sustainability such as environmentally tolerable, socially acceptable, economically feasible and politically desirable. In late 1990’s the crops-livestock systems came to a very important step with intensifying the integration between rice and cattle, in this case through optimization of the manure. The added value of organic fertilizer could reach till 40%. In dairy cattle such a technology was able to benefit Rp 11.000 per cattle per day. In this case, with LEISA (low external input sustainable agriculture) approach, any 8 − 10 liter of milk produced by  a head of cattle needed feed equal to as much as 3 −4 liter of milk only. With LEISA approach the crops-livestock systems has empirically proved the ability of providing job by using the local input efficiently. In improving efficiency, the use of local resources such as local feed and local cattle need to be optimized. To develop the technology that support the concept of crop-livestock systems, the Government could help the farmers through extension so that the farmers willing to use organic fertilizer, especially manure of the cattle. The rice field in the northern part of West Java is a huge potency to produce rice straw as cattle feed. Based on the fact, the beef cattle can be developed in this area so that the manure available to fertilize the rice fields. If the crop-livestock systems is successfully developed in the area, the improve of rice production and productivity is happened, and in turn, the farmers welfare will also increase.   Key words: Farming systems, crops, livestock, organic fertilizer, local resources, crop by product